Randomised clinical trial comparing the effects of acupuncture and a newly designed placebo needle in rotator cuff tendinitis - Kleinhenz, Julia; Streitberger, Konrad; Windeler, Jürgen; Güssbacher, Albert; Mavridis, Georg; Martin, Eike (Pain, 1999)
Acupuncture has gained increasing attention in the treatment of chronic pain. The lack of a satisfying placebo method has made it impossible to show whether needling is an important part of the method or whether the improvement felt by the patient is due to the therapeutic setting and psychological phenomena. Also, the effectiveness of acupuncture has not been demonstrated sufficiently. We treated 52 sportsmen with rotator cuff tendinitis in a randomised single-blind clinical trial using a new placebo-needle as control. Patients were treated for 4 weeks. The primary endpoint of the trial was the change in the modified Constant-Murley-score from the baseline. Assessment of the treatment outcome was made by experienced orthopaedists not informed of the treatment allocation. Acupuncture with penetration of the skin was shown to be more effective than a similar therapeutic setting with placebo needling in the treatment of pain. The acupuncture-group improved 19.2 Constant-Murley-score points (SD 16.1, range from -13 to 50), the control-group improved 8.37 points (SD 14.56, range from -20 to 41), (P=0.014; C.I. 2.3;19.4). This study showed that needling is an important part of the acupuncture effect in the treatment of chronic shoulder pain in athletes. No conclusions can be derived from this study concerning the importance of choosing points and the rules of Traditional Chinese Medicine. Using the new placebo method as control for other ailments could improve the evidence of specific acupuncture effects beyond pain treatment.